Can social comparisons and moral appeals encourage low-emission transport use? - Gessner, Johannes; Habla, Wolfgang; Wagner, Ulrich J. (Transportation research. Part D, Transport and environment, 2024)
Because company cars add to corporate CO2 footprints, companies are beginning to replace cars with mobility budgets that employees can use for leisure and commuting trips. This study examines whether nudges can encourage sustainable travel in such a subsidized setting. We conduct a field experiment with 341 employees of a large German company. Observing expenditure items charged to the mobility budget, we test if social comparisons and a climate-related moral appeal induce a shift towards low-emissions transport modes. We find that simultaneous application of both nudges causes a reduction in car use, particularly taxi and ride sharing, as well as substitution towards micromobility, but not public transport. The social comparison alone is not effective, and the treatment effects of the combined nudge vanish in the second half of the treatment period. Survey evidence suggests that these results are driven by a minority that complies with the communicated social norm.